Liver transplantation in Acute-on-Chronic liver failure: Timing of transplantation and selection of patient population - Li, Xue; Zhang, Liang; Pu, Chunmei; Tang, Shanhong (Frontiers in Medicine, 2022)
Acute-on-Chronic liver failure (ACLF) is a clinical syndrome with high short-term mortality. Alcoholic ACLF is prevalent in European and American countries, while hepatitis B virus (HBV)-related ACLF is more common in the Asia-Pacific region. There is still a lack of a unified definition standard for ACLF, due to various etiologies and pathogeneses in different continents. Currently, liver transplantation (LT) is the most effective treatment for liver failure. However, the shortage of liver sources is still a global problem, which seriously limits the clinical application of an LT. Premature LT aggravates the shortage of liver resources to a certain extent, and too much delay significantly increases the risk of complications and death. Therefore, this study reviews the current literature on LT in the treatment of ACLF and discusses further the challenges for ACLF patients, the timing of LT for ACLF, and the choice of the patient population.